Changes in the Fluorescence Tracking of NaV1.6 Protein Expression in a BTBR T+Itpr3tf/J Autistic Mouse Model - Musaad A. Alshammari; Mohammad R. Khan; Fawaz Alasmari; Abdulaziz O. Alshehri; Rizwan Ali; Mohamed Boudjelal; Khalid A. Alhosaini; Abdurahman A. Niazy; Tahani K. Alshammari (Neural Plasticity)
The axon initial segment (AIS), the site of action potential initiation in neurons, is a critical determinant of neuronal excitability. Growing evidence indicates that appropriate recruitment of the AIS macrocomplex is essential for synchronized firing. However, disruption of the AIS structure is linked to the etiology of multiple disorders, including autism spectrum disorder (ASD), a condition characterized by deficits in social communication, stereotyped behaviors, and very limited interests. To date, a complete understanding of the molecular components that underlie the AIS in ASD has remained elusive. In this research, we examined the AIS structure in a BTBR T+Itpr3tf/J mouse model (BTBR), a valid model that exhibits behavioral, electrical, and molecular features of autism, and compared this to the C57BL/6J wild-type control mouse. Using Western blot studies and high-resolution confocal microscopy in the prefrontal frontal cortex (PFC), our data indicate disrupted expression of different isoforms of the voltage-gated sodium channels (NaV) at the AIS, whereas other components of AIS such as ankyrin-G and fibroblast growth factor 14 (FGF14) and contactin-associated protein 1 (Caspr) in BTBR were comparable to those in wild-type control mice. A Western blot assay showed that BTBR mice exhibited a marked increase in different sodium channel isoforms in the PFC compared to wild-type mice. Our results provide potential evidence for previously undescribed mechanisms that may play a role in the pathogenesis of autistic-like phenotypes in BTBR mice.